$\begin{array}{1 1}(A)\;\large\frac{11}{30}\\(B)\;\large\frac{19}{30}\\(C)\;\large\frac{19}{30}\\(D)\;\text{None of these}\end{array} $

- $P(A\cup B)=P(A)+P(B)-P(A\cap B)$

Step 1:

Given 60 students

n(NCC)=30

n(NSS)=32

$n(NCC\cap NSS)=24$

$\therefore P(NCC)=\large\frac{30}{60}$

$P(NSS)=\large\frac{32}{60}$

$P(NCC \cap NSS)=\large\frac{24}{60}$

Step 2:

P(Students has opted neither NCC or NSS)

$\Rightarrow 1-P$(Students opted for NCC or NSS)

$\Rightarrow 1-\large\frac{38}{60}$

$\Rightarrow \large\frac{60-38}{60}$

$\Rightarrow \large\frac{22}{60}$

$\Rightarrow \large\frac{11}{30}$

Hence (A) is the correct answer.

Ask Question

Tag:MathPhyChemBioOther

Take Test

...